Incidence and outcomes of unstable angina compared with non-ST-elevation myocardial infarction. Issue 18 (24th April 2019) - Puelacher, Christian; Gugala, Mathias; Adamson, Philip D; Shah, Anoop; Chapman, Andrew R; Anand, Atul; Sabti, Zaid; Boeddinghaus, Jasper; Nestelberger, Thomas; Twerenbold, Raphael; Wildi, Karin; Badertscher, Patrick; et al.
Abstract : Objective: Assess the relative incidence and compare characteristics and outcome of unstable angina (UA) and non-ST-elevation myocardial infarction (NSTEMI). Design: Two independent prospective multicentre diagnostic studies (Advantageous Predictors of Acute Coronary Syndromes Evaluation [APACE] and High-Sensitivity Troponin in the Evaluation of Patients With Acute Coronary Syndrome [High-STEACS]) enrolling patients with acute chest discomfort presenting to the emergency department. Central adjudication of the final diagnosis was done by two independent cardiologists using all clinical information including serial measurements of high-sensitivity cardiac troponin (hs-cTn). All-cause death and future non-fatal MI were assessed at 30 days and 1 year. Results: 8992 patients were enrolled at 11 centres. UA was adjudicated in 8.9%(95% CI 8.0 to 9.7) and 2.8% (95% CI 2.3 to 3.3) patients in APACE and High-STEACS, respectively, and NSTEMI in 15.1% (95% CI 14.0 to 16.2) and 13.4% (95% CI 12.4 to 14.3). Coronary artery disease was pre-existing in 73% and 76% of patients with UA. At 30 days, all-cause mortality in UA was substantially lower as compared with NSTEMI (0.5% vs 3.7%, p=0.002 in APACE, 0.7% vs 7.4%, p=0.004 in High-STEACS). Similarly, at 1 year in UA all-cause mortality was 3.3% (95% CI 1.2 to 5.3) vs 10.4% (95% CI 7.9 to 12.9) in APACE, and 5.1% (95% CI 0.7 to 9.5) vs 22.9% (95% CI 19.3 to 26.4) in High-STEACS, and similar to non-cardiac chest pain (NCCP). In contrast, future non-fatal MI in APACE was comparable in UA and NSTEMI (11.2%, 95% CI 7.8 to 14.6 and 7.9%, 95% CI 5.7 to 10.2), and higher than in NCCP (0.6%, 95% CI 0.2 to 1.0). Conclusions: The relative incidence and mortality of UA is substantially lower than that of NSTEMI, while the rate of future non-fatal MI is similar.